The Paradox of the Moral Irrelevance of the Government and the Law: A Critique of Carlos Nino's Approach - Cianciardo, Juan Carlos Mariano (2012)
Some authors have speculated about the fact that if the law were connected to morality, then it would not be relevant, because morality would be enough to regulate social life. A study of this objection to the connection thesis will be outlined in this paper. In other words, the possible answers to the question about the practical difference that law gives to morality will be analyzed. The work of the Argentine philosopher Carlos Nino will be taken as the starting point for this task.